2017
DOI: 10.1007/s00167-017-4627-2
|View full text |Cite
|
Sign up to set email alerts
|

Coronal femoral TKA position significantly influences in vivo patellar loading in unresurfaced patellae after primary total knee arthroplasty

Abstract: Diagnostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 32 publications
(51 reference statements)
2
50
0
2
Order By: Relevance
“…The second important finding of the present study was that the factorial analysis proved a clinical and radiological significant correlation among regions belonging to the same knee compartment. Regions belonging to the same knee compartment are in a close biomechanical relation with each other's and consequently, the correlations seen between the rmBTU scores inside the same knee compartment are in accordance with the actual literature …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The second important finding of the present study was that the factorial analysis proved a clinical and radiological significant correlation among regions belonging to the same knee compartment. Regions belonging to the same knee compartment are in a close biomechanical relation with each other's and consequently, the correlations seen between the rmBTU scores inside the same knee compartment are in accordance with the actual literature …”
Section: Discussionsupporting
confidence: 88%
“…Single‐photon emission computed tomography together with computed tomography (SPECT/CT) is increasingly gaining importance for assessment of bony pathologies including cartilage lesions and osteoarthritis (OA) of the lower extremity . The first line imaging for knee OA still is standardized weight‐bearing radiographs (anteroposterior, lateral, and patellar sunrise view).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Slevin et al 19 also reported on the effects of tibial alignment on patellar stress in their study. They found no correlation between the bone tracer uptake in the patella and the TTTG distance.…”
Section: Implant Factorsmentioning
confidence: 85%
“…Ein CT ist zum einen zur Bestimmung der Komponentenrotation hilfreich [6] Unter Verwendung spezieller Metallartefaktunterdrückung (z. B. i-MAR) können auch Lockerungssäume und Osteolysen gut dargestellt werden.…”
Section: Computertomografie (2-d 3-d)unclassified